Red Cell Distribution Width and Its Relationship with Microalbuminuria Among Patients with Essential Hypertension - T, Akhshaya Ponsuba; D, Manimaran; K, Desigamani; B S, Sangeetha; H, Rajesh; J, Sheeja (Annals of Pathology and Laboratory Medicine, 2019)
Background: Elevated Red Cell Distribution Width (RDW) is an indicator of renal damage in hypertensive patients. Microalbuminuria (MAU) is an indicator of risk for cardiovascular complications and progressive renal damage in patients with diabetes and also hypertension. Objectives: 1. Determine RDW and microalbuminuria in hypertensive patients. 2. Determine RDW levels in hypertensive patients with microalbuminuria and without microalbuminuria and to evaluate the relationship between these two parameters. Methodology: Our prospective study was conducted on 98 patients attending outpatient clinic for blood pressure check up and treatment. For measurement of RDW - 2 ml blood was collected by clean venepuncture and collected in EDTA tube and determined RDW by automatic cell counter (sysmex KX-21) and for microalbuminuria - Early morning urine samples were collected and microalbumin determined by immunoturbidimetry. Statistical analysis were done using SPSS version – 16.0. Results: A total of 98 patients were included in the present study with age ranging from 30 – 86 year. All the patients were known hypertensive under treatment and 54 of them also had associated diabetes mellitus. The male to female ratio of the sample was 29:69. Out of the total 98 patients, 58 (59.2%) presented with microalbuminuria and 23 (23.5%) patients had RDW value above normal. Out of the 58 patients with microalbuminuria, 17 (29.3%) patients had RDW value above normal but only 6 (15%) patients out of 40 patients without microalbuminuria had RDW value above normal. Conclusion: Though we could not find out a direct relationship between RDW and MAU, some of the individual patients with MAU had high RDW compared to patients without MAU. As RDW is routinely done as part of complete blood counts in all patients, if its value is high in hypertensive patients, we can workup the patient for microalbuminuria. Early detection and treatment can avoid complications in these patients.